A Bioengineering Approach to Myopia Control Tested in a Guinea Pig Model - Garcia, Mariana B. (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: To investigate the biocompatibility of an injectable hydrogel and its ability to control myopia progression in guinea pigs. METHODS: The study used a hydrogel synthesized from acrylated hyaluronic acid with a conjugated cell-binding peptide and enzymatically degradable crosslinker. Seven-day-old guinea pigs were first form deprived (FD) with diffusers for 1 week. One group was kept as an FD-only control; two groups received a sub-Tenon's capsule injection of either hydrogel or buffer (sham surgery) at the posterior pole of the eye. Form deprivation treatments were then continued for 3 additional weeks. Treatment effects were evaluated in terms of ocular axial length and refractive error. Safety was evaluated via intraocular pressure (IOP), visual acuity, flash electroretinograms (ERG), and histology. RESULTS: Both hydrogel and sham surgery groups showed significantly reduced axial elongation and myopia progression compared to the FD-only group. For axial lengths, net changes in interocular difference (treated minus control) were 0.04 ± 0.06, 0.02 ± 0.09, and 0.24 ± 0.08 mm for hydrogel, sham, and FD-only groups, respectively (P = 0.0006). Intraocular pressures, visual acuities, and ERGs of treated eyes were not significantly different from contralateral controls. Extensive cell migration into the implants was evident. Both surgery groups showed noticeable Tenon's capsule thickening. CONCLUSIONS: Sub-Tenon's capsule injections of both hydrogel and buffer inhibited myopia progression, with no adverse effects on ocular health. The latter unexpected effect warrants further investigation as a potential novel myopia control therapy. That the hydrogel implant supported significant cell infiltration offers further proof of its biocompatibility, with potential application as a tool for drug and cell delivery.